Ectopic thyroid mass separately present in mediastinum and not a retrosternal extension: a rare case report - Budhiraja, Grace; Singh, Harsimrat; ., Harpreet; ., Prabhjot; Goyal, Nischai (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Retrosternal extension of goiter is one of the most common types of masses in the superior mediastinum. These types of goiters classically present with compressive symptoms such as dyspnoea, dysphonia, dysphagia, or sleep apnea. Surgical treatment with a total thyroidectomy and complete removal of the intrathoracic portion of thyroid is the gold standard treatment. These cervico-mediastinal lesions at times may not be continuous, and a sternotomy may be required for complete and safe excision of the mediastinal mass to achieve decompression of the surrounding structures and preventing the hemorrhagic complications if attempted from cervical incision.